Rapid access rehabilitation after exacerbations of COPD – A qualitative study. (September 2021) - Oliveira, Ana; Quach, Shirley; Alsubheen, Sanaa; Dasouki, Sabrina; Walker, Jan; Brooks, Dina; Goldstein, Roger
Abstract: Purpose: Rehabilitation after acute exacerbations of chronic obstructive pulmonary disease (AECOPD) is beneficial, but its feasibility is questionable. Feasibility is potentiated by stakeholder involvement during program development. We aimed to explore the perspectives of various stakeholders towards an innovative rapid access rehabilitation (RAR) program for patients immediately following hospitalization for an AECOPD. Method: Semi-structured interviews were conducted with patients recently hospitalized for AECOPD, healthcare professionals (HCP) and policymakers providing care for such patients. Thematic analysis was performed. Results: Three patients (1 female; 62–89 years; GOLD D), ten HCP (3 females, 31–71 years) and three policymakers (3 females, 38–55 years) participated. Patients, HCP and policymakers shared similar visions for the development of a RAR program. Five main themes and ten subthemes were identified. They comprised: Pre-RAR aspects (Management properties, Eligibility), RAR program (Outcomes, Structure, Components), RAR optimization (Referral, Uptake), Partnership (Collaboration, Dedicated Coordinator) and COVID-19 (Adaptations). Essential elements included: identifying clear eligibility criteria, addressing patients' needs at the time of hospital discharge, having a structured education and self-management program and modifying to respond to unexpected events (e.g., COVID). Suggestions to optimize referrals included a clear referral pathway, improving program awareness, assigning dedicated care coordinators to provide patient support throughout the program and establishing strong partnerships among different care settings and providers. Conclusions: Identifying the essential program elements and approaches to optimize referrals, were considered to be key design approaches for success in establishing RAR. Highlights: Different stakeholders share similar visions for an RAR program. The main RAR components are physical and mental health and social support. A care coordinator is essential to the sustainability and effectiveness of an RAR.